2020
DOI: 10.1002/qua.26192
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional confined hydrogen: An entropy and complexity approach

Abstract: The position and momentum spreading of the electron distribution of the two-dimensional confined hydrogenic atom, which is a basic prototype of the general multidimensional confined quantum systems, is numerically studied in terms of the confinement radius for the 1s, 2s, 2p, and 3d quantum states by means of the main entropy and complexity information-theoretical measures. First, the Shannon entropy and the Fisher information, as well as the associated uncertainty relations, are computed and discussed. Then, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 92 publications
(172 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, information-theoretic measures have been shown to display interesting behaviour in confined systems [55,56]. Recently, Estañón et al [48] and Salazar et al [57] have studied entropic measures of 2-D and 3-D confined hydrogenic systems. The latter study focused on the behaviour of the Shannon entropy of confined 3-D hydrogenic systems, where it was shown that the competition between Coulombic and hard wall potential leads to interesting features or structures in the entropy sum as a function of the confinement radius.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, information-theoretic measures have been shown to display interesting behaviour in confined systems [55,56]. Recently, Estañón et al [48] and Salazar et al [57] have studied entropic measures of 2-D and 3-D confined hydrogenic systems. The latter study focused on the behaviour of the Shannon entropy of confined 3-D hydrogenic systems, where it was shown that the competition between Coulombic and hard wall potential leads to interesting features or structures in the entropy sum as a function of the confinement radius.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of dimensionally confined hydrogen atom is of interest in various branches of physics like semiconductor physics, material sciences, astrophysics, condensed matter physics, plasma physics and atomic and molecular physics [2]. Hydrogenic atoms confined in one and two dimensions have been well studied [1][2][3][4][5][6][7][8][9][10][11]. Historically, the 2D hydrogen problem was introduced as a leading approximation for the electron motion in a highly anisotropic crystal [12].…”
Section: Introductionmentioning
confidence: 99%
“…The present work deals with a non-relativistic 2D hydrogen atom spatially bounded in a circular region with impenetrable boundary [6][7][8][9]. Since an exciton is a hydrogen-like bound state of an electron and a hole, the motivation for this study is based on the practical applications to the systems of excitons in the heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…There exists an increasing interest in the study of diverse quantum confined systems by means of the theoretical information methods [26][27][28][29][30][31][32]39]. In information theory, entropy is a measure of the uncertainty associated with a random variable.…”
Section: Introductionmentioning
confidence: 99%